Pemanfaatan Kedelai menjadi Tempe untuk Keterampilan dan Kemandirian Masyarakat Desa Cahaya Makmur, Sungkai Jaya, Lampung Utara - Citra Nurmania Putri; Darotul Asih Fatun Nikmah; Dany Arsenio; Bayu Akbar Saputra; Azzis Kurniawan; Della Puspita Sari; Dalih Prayogi; Devita Rezkia Amanda; Dhiya Ghina Sholiha; Dhaisya Dea Maretha; Buyung Syukron (Lembaga Pengembangan Kinerja Dosen, 2025)
Nutritious food plays an important role in maintaining health and increasing community productivity. However, protein consumption in Indonesia remains low despite the widespread cultivation of soybeans, the main source of vegetable protein. Tempe, a traditional soybean product, is highly nutritious, easy to produce, and popular among the community. In Hamlet 1 (Mangga Tiga), Cahaya Makmur Village, North Lampung, most residents grow soybeans but still buy tempe from outside the village. This indicates that the harvest has not been optimally utilized, either for consumption or economic purposes. To address this issue, students from the UIN Jurai Siwo Lampung Community Service Program (KKN), Period II Group 8, conducted training on tempeh production. The aim was to improve residents' skills in processing soybeans into nutritious food while also opening up business opportunities. The training lasted 43 days using a Participatory Action Research (PAR) approach, involving the community in the stages of problem identification, planning, implementation, and evaluation. A total of 25 participants attended, consisting of housewives, village officials, and local residents. They practiced the entire tempeh-making process, from washing, soaking, boiling, adding yeast, to fermentation. The production results were high-quality tempeh with a white color, firm texture, and distinctive aroma. Participants responded positively, gained new knowledge, and were motivated to make tempeh independently and develop it into a small business. This activity successfully increased the utilization of soybean harvests and demonstrated the potential for food self-sufficiency and economic empowerment in Cahaya Makmur Village.